2017
DOI: 10.1016/j.psychres.2017.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular stimulation improves insight into illness in schizophrenia spectrum disorders

Abstract: Impaired insight into illness (IMP-INS) is common among individuals with schizophrenia spectrum disorders (SSD), contributing to medication nonadherence and poor clinical outcomes. Caloric vestibular simulation (CVS) is typically used to assess peripheral vestibular system function. Left cold CVS is also a transiently effective treatment for IMP-INS and hemineglect secondary to right brain hemisphere stroke, and possibly for IMP-INS and mood stabilization in patients with SSD. Participants with SSD and moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
(89 reference statements)
1
8
0
Order By: Relevance
“…The third study corresponds to a randomized clinical trial published by Gerretzen, where caloric stimulation with water at 4°C was applied sequentially in the right ear and left ear of patients within the spectrum of schizophrenia. This study showed improvement in symptoms and of the insight that lasted approximately 30 minutes after application of the cold water in the left ear [30].…”
Section: Caloric Vestibular Stimulationsupporting
confidence: 55%
“…The third study corresponds to a randomized clinical trial published by Gerretzen, where caloric stimulation with water at 4°C was applied sequentially in the right ear and left ear of patients within the spectrum of schizophrenia. This study showed improvement in symptoms and of the insight that lasted approximately 30 minutes after application of the cold water in the left ear [30].…”
Section: Caloric Vestibular Stimulationsupporting
confidence: 55%
“…If there is no disease-free baseline to which to return, what does this mean for the applicability of sensory neuromodulation? Gerretsen et al (2017) used irrigation-based CVS with schizophrenia subjects and found evidence of transiently improved insight to illness. The authors concluded that, similar to hemispatial neglect, CVS acted to balance activity in the two hemispheres, making use of the potential of unilateral CVS to preferentially activate one hemisphere.…”
Section: Why It Helps and Doesn't Hurtmentioning
confidence: 99%
“…Compromised white matter integrity in the splenium could represent a marker or therapeutic target to improve illness awareness and treatment adherence in patients with Imp-IA in schizophrenia. 8,40 Evidence suggests that illness awareness in schizophrenia 19,20,41 and other neuropsychiatric conditions (i.e., stroke) 4244 can be transiently improved with the use of noninvasive neurostimulation techniques, such as transcranial magnetic, direct current, and vestibular stimulation by enhancing interhemispheric function. In particular, three studies found marked improvements in Imp-IA in patients with schizophrenia after the application of fronto-temporoparietal transcranial direct current stimulation, which involved inhibitory cathodal stimulation of the left parietal area.…”
Section: Discussionmentioning
confidence: 99%